2017
DOI: 10.5755/j01.ee.28.3.16115
|View full text |Cite
|
Sign up to set email alerts
|

How Does 5s Implementation Affect Company Performance? A Case Study Applied to a Subsidiary of a Rubber Goods Manufacturer from Serbia

Abstract: 5S can be viewed as a system of workplace rules devised to create a safe and productive work environment and to provide efficient and effective realization of business tasks. Its implementation is expected to reduce defects, improve quality, increase safety and the morale of the employees, and improve employees' productivity. In the present paper, over the period of seven years, we investigate the case of a rubber goods manufacturer from Serbia which has implemented 5S in one of its subsidiaries. To assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…The statistically significant relationship between specific IE method and the higher performance measured by ROE 1 or ROE 2 was observed only for standardization, 5S, JIT, APS and six sigma. The research essentially confirmed the prevailing view that the selected IE methods positively affect business performance and competitiveness (Huarng, 2002;Fullerton & Wempe, 2009;Yang et al, 2011;Nawanir et al, 2012;Danese et al, 2012;Todorovic & Cupic, 2017). Although the studies mentioned above (including ours) focus on the overall performance only with different indicators, none of the above used the ROE indicator.…”
Section: Discussionsupporting
confidence: 82%
“…The statistically significant relationship between specific IE method and the higher performance measured by ROE 1 or ROE 2 was observed only for standardization, 5S, JIT, APS and six sigma. The research essentially confirmed the prevailing view that the selected IE methods positively affect business performance and competitiveness (Huarng, 2002;Fullerton & Wempe, 2009;Yang et al, 2011;Nawanir et al, 2012;Danese et al, 2012;Todorovic & Cupic, 2017). Although the studies mentioned above (including ours) focus on the overall performance only with different indicators, none of the above used the ROE indicator.…”
Section: Discussionsupporting
confidence: 82%
“…Implementing the 5S method is one of the first steps in the Lean Manufacturing strategy, and impacts the behavior of the Lean System method. Dana [45] and Veres et al [68] have determined, as a result, that there is an increase in organizational productivity, accompanied by improvements in operational and profitability indicators in the short, long and medium terms, as well as in manufacturing costs, with a positive impact on profitability [69][70][71][72]. The "5 Whys" is a technique that uses a systematic approach to problem-solving in order to find the root cause of a defect or problem [73].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It shows how many monetary units of operating profit are generated for each monetary unit that the company has invested in business assets, regardless of the method of obtaining them. The rate of return on equity (ROE) as the ratio of net results and average equity of the company, is probably the most important accounting ratio that measures the "lower limit" of the company's performance and takes into account the interests of shareholders (Knežević et al, 2019, p.95), whereat it cannot be said that this indicator is not important for the company management (Todorović & Čupić, 2017). Since in modern organizations managers are responsible for the successful use of share capital, this indicator is often called the managers' efficiency ratio (Račić et al, 2011).…”
Section: Source: Authors Based On the Financial Statements Of The Observed Companymentioning
confidence: 99%